Pengembangan Bahasa Anak Usia Dini dalam Memahami Tema Cerita Pendek - Fika Septiana Sari (SELING: Jurnal Program Studi PGRA, 2016)
The purpose of writing this article is to assess comprehension and language development of children in understanding the theme of the short story by paying attention to the images and use simple words to express the curiosity of children, and be able to know and understand the implications of language development of children in understanding the theme of short story paying attention to the images and use simple words to express the children's curiosity. The method of writing this article is through the study of literature and the initial observation by finding multiple sources of information relevant to the purpose of writing the article. From some literature synthesis is then carried out to see the relationship between early childhood language development by understanding the theme of the short story. The results of the discussion showed that the development of language through peahaman story themes pedek with good language development of children in understanding the theme of the short story by paying attention to the images and use simple words to express the curiosity of children in the age range 12 - <24 months are already visible and in accordance with the TPP at the Permendiknas No. 58 of 2009